2008
DOI: 10.1162/pres.17.4.405
|View full text |Cite
|
Sign up to set email alerts
|

Improving Presence Theory Through Experiential Design

Abstract: Despite ongoing research over the last 15 years, the presence construct remains somewhat limited in its ability to be applied beyond the sensory domain. In order to increase its usefulness for applied challenges (e.g., using presence theory to enhance simulators' effectiveness), a discussion about a new conceptualization of presence is introduced. This novel perspective on presence is rooted in the notion of "experiential design," an approach businesses use to create strategically compelling and memorable expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 35 publications
1
21
0
1
Order By: Relevance
“…As a consequence, better performances can be achieved (Barfield et al 1995). The enhancement of the sense of presence theorized in Chertoff et al (2008) was experimentally confirmed in the study reported in Chertoff et al (2010).…”
Section: Experiential Designsupporting
confidence: 55%
See 3 more Smart Citations
“…As a consequence, better performances can be achieved (Barfield et al 1995). The enhancement of the sense of presence theorized in Chertoff et al (2008) was experimentally confirmed in the study reported in Chertoff et al (2010).…”
Section: Experiential Designsupporting
confidence: 55%
“…In the context of VR, ED has been proposed as a method to enhance presence in VEs (Chertoff et al 2008). Table 1 (middle column) reports the five dimensions of ED applied toward VEs, as illustrated in Chertoff et al (2010).…”
Section: Experiential Designmentioning
confidence: 99%
See 2 more Smart Citations
“…There exist affective and cognitive elements, or endogenous factors, that contribute to a holistic experience beyond the physical location and the tasks performed. There is much emerging support within the literature for a relationship between presence and holistic experiences [7][10] [17]. In fact, several researchers have begun to look towards commercial video games to better understand how presence is affected through holistic virtual environments [4][8] [19] [27].…”
Section: Introductionmentioning
confidence: 99%